(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To examine the clinical characteristics of fungal nail infection and related factors among patients from the National Hospital of Dermatology and Venereology in 2018. Methods: Cross-sectional descriptive study on 110 patients with diagnosis of fungal nail infection by positive fungal culture at the National Hospital of Dermatology & Venereology from August 2018 to July 2019. Results: The age group affected mostly by the disease is working age group of 20-59 years old, accounting for 70%, in which women accounted 61.3%. The proportion of patients living in rural areas is 2.66 times higher than the proportion of patients living in urban areas. Common occupations affected by the disease included manual workers such as farmers, people in contact with pets, livestock, or poultry (38.2%) and workers working frequently in wet environments (19.1%). The most common clinical manifestation was distal and lateral subungual onychomycosis, accounting for (71/110, 64.5%), followed by proximal subungual onychomycosis (48/110, 43.6%) and superficial white onychomycosis (38/110, 34.5%). The lesion with crumbly subungual hyper-keratosis was mainly observed, accounting for (53/110, 48,2%). Among 110 patients with positive fungal culture, 96 patients (87.3%) had positive KOH examination and 14 patients (12.7%) patients had negative KOH examination. Conclusion: Fungal nail infection was common in people of working age, especially those worked in humid environments. The most common clinical manifestations were distal and lateral subungual onychomycosis and crumbly subungual hyperkeratosis. Eighty-seven point three percent of patients had similar results between KOH examination and culture, showing the high reliability of KOH examination in diagnosing fungal nail infection.